Examination of mullite ceramic specimens made by conventional casting method from kaolin and sawdust. (April 2020) - Kurovics, E; Ibrahim, J F M; Tihtih, M; Udvardi, B; Nuilek, K; Gömze, L A
Abstract: Using relatively low-cost raw materials (conventional kaolin and sawdust powders) and simple technology, the authors have developed new ceramic composite materials which can successfully meet different industrial requirements. Casting masses (slurries) were made by mixing and milling different compositions of the powders with distilled water. The ceramic specimens were made by conventional gravitation slipcasting method, after drying of the green specimens, the samples were sintered in an electric kiln under oxidation and reduction atmosphere at 1250°C. The prepared and sintered specimens were tested based on geometrical sizes, microstructures and morphologies using scanning electron microscopy. In this work, the authors present some parts of the results of their research and investigation.